1992
DOI: 10.1007/bf00314866
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vinorelbine in man

Abstract: The pharmacokinetics of vinorelbine has been investigated by a new HPLC method in 8 cancer patients receiving 8 weekly doses (30 mg.m-2) administered by brief infusion (15 min). The plasma concentration-time curves showed a tri-exponential decay with a long terminal half-life (44.7 h) and a high volume of distribution (Vz = 75.61.kg-1). The concentrations after the 8th infusion were significantly lower than after the 1st infusion, but without significant modification of CL (1.28 l.h-1.kg-1) or AUC (0.80 mg.l-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 6 publications
5
9
1
Order By: Relevance
“…The PK of pemetrexed and vinorelbine were consistent with data obtained with single-agent chemotherapy (Marquet et al, 1992;Leveque and Jehl, 1996;Sabot et al, 1998). There was no evidence for PK interaction between the two drugs.…”
Section: Discussionsupporting
confidence: 80%
“…The PK of pemetrexed and vinorelbine were consistent with data obtained with single-agent chemotherapy (Marquet et al, 1992;Leveque and Jehl, 1996;Sabot et al, 1998). There was no evidence for PK interaction between the two drugs.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, systemic exposure was lower at a given dose compared with that reported in previous adult studies but was proportionate to clearance. The calculated area under the plasma concentration-time curve in this study at 30 mg/m 2 was 676 ng/mL-h compared with 800 to 900 ng/mL-h reported in adult patients (19,20). Thus, we believe that a weekly schedule of i.v.…”
Section: Discussionmentioning
confidence: 39%
“…4,5 The elimination half-life after intravenous administration is 42 to 45 hours and 24 to 56 hours after oral administration. 5,6 Pharmacokinetics in elderly patients (older than 65 years) is similar to those reported in younger people. 7 This report reviews the most important studies involving Vinorelbine in ABC with particular regard to the results of randomized trials in order to evaluate its role in this subset of patients.…”
Section: Introductionsupporting
confidence: 55%